Mecanización para la agricultura sostenible: los enfoques tecnológicos en la agricultura y el cambio de énfasis de labranza convencional a conservacionistas - Pinto Falconi, Lázzaro Joaquín (2021)
Agriculture developed as a continuous process, according to the technological, economic and social trends of the different times that have elapsed. Before carrying out any analysis or projection in agricultural scenarios, it is necessary to consider what is the type of agriculture or technological approach, since it is sometimes observed that there is no correspondence between the characteristics of the production system, the agricultural technology that exists and the plans for introduction of new technologies, production, marketing and others. Mechanization transforms the work factor into a productive factor. This shows one of the roles that agricultural mechanization can play as an input for production: with the proper use of appropriate technology, better performance of other inputs such as fertilizers and other chemicals, high-quality seeds and water can be ensured. Proper mechanization can improve energy efficiency in agricultural production, which in turn improves sustainability and productive capacity and reduces damaging effects on the environment. It will depend on the ability of farmers to make the right technological decisions taking into account both its short and long term implications. Over the years’ agriculture has evolved due to the integration of technology in the processes. However, of all the modern agricultural technologies introduced in developing countries, mechanization is probably the most controversial. It has been attributed the exacerbation of rural unemployment and its contribution to other social ills.